2018
DOI: 10.1364/ol.43.004184
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-linewidth single-frequency photonic microwave generation in optically injected semiconductor lasers with filtered optical feedback

Abstract: A narrow-linewidth single-frequency photonic-microwave-generation scheme using an optically injected semiconductor laser with a filtered optical feedback has been proposed. The filtered feedback comes from a single feedback loop, which includes a narrow bandpass filter. With the filtered feedback, the linewidth of the generated microwave can be significantly reduced from 22.4 MHz to 9.0 kHz, with the side peaks suppression of 28 dB. The proposed scheme shows superior performance compared to the conventional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…7. It can be seen from the figure that the employing of optical feedback can generate the ECMs close to the microwave frequency f , [39] and the mode interval is approximately equal to 1/τ. As the τ increases, the ECMs will become denser.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…7. It can be seen from the figure that the employing of optical feedback can generate the ECMs close to the microwave frequency f , [39] and the mode interval is approximately equal to 1/τ. As the τ increases, the ECMs will become denser.…”
Section: Resultsmentioning
confidence: 92%
“…4(a2), (b2), and (c2), some strong sidebands can be observed around the microwave frequency f , which are attributed to the external cavity modes (ECMs) excited by the external optical feedback. [12,14,39] The frequency interval between two adjacent sidebands is about 416.7 MHz, which is approximately equal to the reciprocal of the feedback time τ (= 2.4 ns). In the following discussion, the effect of feedback parameters on the microwave linewidth is studied systematically.…”
Section: Resultsmentioning
confidence: 99%
“…For example, under stable emission, the laser emits light at the injected wavelength (the so-called injection-locking region) and has a high resonance frequency and a large modulation bandwidth, 3 which have broad applications for optical communications. The regular pulsing regime can be used for microwave generation, 4,5 while the broadband chaotic signal can be exploited for ultrafast random number generation. 6 In turn, the output of the laser in the chaotic regime can be used for testing new methods for data analysis, and in particular, for time series prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear dynamics of semiconductor lasers with optical feedback has been intensively investigated [1,2], not only because of its interest as an experimental test bed to study nonlinear phenomena, but also, because it has found many practical applications [3], including random number generation [4][5][6][7], photonic microwave generation [8][9][10], chaotic lidar [11], compressive sensing [12] to name just a few. Recent experimental and theoretical studies have demonstrated that the high-dimensional feedback-induced dynamics can be exploited for neuromorphic computing, using the reservoir computing paradigm [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%